Báo cáo lồng ghép vấn đề bình đẳng giới trong dự án Luật Dầu khí (sửa đổi) (Số: 81/BC-BCT) - Bộ Công thương (2022)
Toàn văn Báo cáo lồng ghép vấn đề bình đẳng giới trong dự án Luật Dầu khí (sửa đổi) (Số: 81/BC-BCT)